EVALUASI FUNGSIONAL DAN STRUKTURAL PERKERASAN LENTUR PADA JALAN NASIONAL BANDUNG-PURWAKARTA DENGAN METODE AUSTROADS 2011 - Seno Saputro; Eri Susanto Hariyadi (Himpunan Pengembangan Jalan Indonesia (HPJI), 2015)
Abstract To maintain the level of service of a road needs a proper evaluation method, both structural and functional evaluations. Austroads method 2011 is a method that has been accommodating resistance to fatigue cracking, which is a reference for use in Indonesia. In this study the Austroads method 2011is examined whether if it can be implemented in Indonesia. Structural evaluations conducted based on data obtained from the Falling Weight deflectometer while functional evaluation conducted based on data obtained from the roughness NAASRA tool. The results indicate that the DSAR7 value obtained by the Austroads 2011 method is quite identical to the value generated by the CESAL Bina Marga method. The implementation of Austroads 2011 method for road conditions in Indonesia needs to consider several things, namely pavement structure modeling, types of vehicles, as well as the